Puerarin for OVX-Induced Postmenopausal Osteoporosis in Murine Model: Systematic Review and Meta-Analysis - Yang, Xiaobin; Zheng, Haishi; Liu, Yuan; Hao, Dingjun; He, Baorong; Kong, Lingbo (Current Stem Cell Research & Therapy, 2020)
Aims/Background: Ovariectomy (OVX)-induced murine model is widely used for postmenopausal osteoporosis study. Our current study was conducted to systematically review and essentially quantified the bone mass enhancing effect of puerarin on treating OVX-induced postmenopausal osteoporosis in murine model. Methods: Literatures from PUBMED, EMBASE, and CNKI were involved in our searching strategy by limited the inception date to January 9th, 2019. Moreover, the enhancing effect of puerarin on bone mass compared to OVX-induced rats is evaluated by four independent reviewers. Finally, all the data were extracted, quantified and analyzed via RevMan, besides that in our current review study, we assessed the methodological quality for each involved study. Results: Based on the searching strategy, eight randomization studies were finally included in current meta-analysis and systematic review. According to the data analysis by RevMan, puerarin could improve bone mineral density (BMD); (eight studies, n=203; weighted mean difference, 0.05; 95% CI, 0.03-0.07; P<0.0001) using a random-effects model. There is no significant difference between puerarin and estrogen (seven studies, n=184; weighted mean difference, 0.00; 95% CI, -0.01 to 0.00; P=0.30). Conclusion: Puerarin showed upregulating effects on bone mass in OVX-induced postmenopausal osteoporosis in murine model. More studies of the effect of puerarin on bone density in OVX animals are needed.
Keywords: Puerarin